Multiple myeloma in the mandible of a 30-year old female: A Case Report - Abdal, Khadijeh; Hafezi Ahmadi, Mohammadreza; Kazemi, Hamidreza (Journal of Dental School, 2019)
Multiple myeloma (MM) is a relatively rare malignant hematological disease, which is characterized by multicentric proliferation of plasma cells in the bone marrow. It is typically a disease of adults, with men being affected slightly more often than women. The median age at diagnosis is between 60 and 70 years, and it is rarely diagnosed before the age of 40. Although any bone may be affected, the jaws have been reported to be involved in about 30% of cases while its occurrence in the maxilla is very common. We present a case of MM in the mandible of a 30- year-old female patient.